ENERGY DISPERSION X-RAY FLUORESCENCE ANALYSIS FOR ENVIRONMENT PROTECTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
Environmental monitoring is aimed mostly at pollution levels change tendency estimation and high sensitive analysis methods are applied for this purpose. X-Ray fluorescence analysis (RFA) allows getting information of metal content in ten or hundred seconds. The analyzers with Si(Li) detectors were used for measurements. Our report deals with some examples which are given as new RFA methods (with secondary target) application in the laboratory and field conditions.